Experimental Research of the Energy Efficiency of Accelerated Thermal Tests of Traction Electric Machines - Vasyliev, V. Y; Afanasov, A. M; Hulivets, O. M.; Popudniak, Y. Y (Science and Transport Progress, 2022)
Purpose. Heating tests of traction electric machines are the most energy-intensive tests. Taking into account the need to choose a rational variant of the mutual load scheme in order to reduce the consumption of electrical energy during the tests, a study of the amount of total useful energy of the power sources of the stand at hourly and starting current was carried out. Methodology. Experimental studies were carried out on a mutual load stand. Rotating machines were used as power sources (voltage booster and linear generator). The voltage and field attenuation coefficient of the traction motors during the tests were kept nominal. The condition of the equality of the final temperature excesses of the tested traction motors for both test modes was the achievement of the same total circuit resistance. For analysis of test results, methods of theoretical research and analytical calculation of electric circuits, theoretical foundations of electrical engineering, mathematical modeling of electrical and energy processes were used. Findings. The conducted set of tests on heating the traction motors of electric rolling stock practically showed that the consumption of electrical energy at the starting current is 36% lower compared to the hourly load mode. Tests on the mutual load stand confirmed the practical possibility of accelerated tests of traction electric motors. Originality. It has been practically proven that the use of the heating test mode with the starting current ensures an increase in the energy efficiency of the tests and a corresponding reduction in the total electricity consumption for acceptance tests. Further development of practical research is planned for the purpose of determining energy saving reserves during post-repair tests of traction electric motors of highway, quarry and suburban transport. Practical value. The results of practical tests can become the basis for modernization of mutual load stands of locomotive repair enterprises for thermal tests of traction motors of direct and pulsating current. The conducted tests allow us to create recommendations for the design of rational schemes of test benches with increased energy efficiency of the system of mutual loading of traction electric machines, which differ by accounting the efficiency of sources and power converters.